Influence of Method of Fixing Resin Lips on Resin Yields from Chir Pine (Pinus roxburghii Sargent) - Mathauda, G. S. (Indian Forester, 1960)
Results of two experiments on the comparative merits of nailed-lips as against the wood-inserted ones are presented. Data collected during the course of this work show that nailed-lips give 11% and 18% better yield during the first and second years tapping of new channels respectively. It has also been observed that difference in yields of resin from blazes placed on the eastern and western faces of trees is not significant.